(untitled) (Nonconventional Technologies Review, 2020)
This paper presents the potential application of electrical discharge machining using wire on high hardness aerospace materials, such as titanium alloy Ti-6Al-4V annealed beta-extruded. The paper presents the general context of the current aerospace product requirements with relation to the machining of close tolerance samples for mechanical properties testing. It shows the general principle of wire electrical discharge machining (Wire EDM) as well as the equipment configurations available on the market. Details are provided related to aerospace materials, with emphasis on titanium alloy Ti-6Al-4V and the current requirements related to the material testing. In depth description of the tensile testing samples is given as an input to the proposed solution which applies the Wire EDM technology to the titanium alloy Ti-6Al-4V aerospace material in order to provide an improved solution to conventional machining.